2021
DOI: 10.5056/jnm20135
|View full text |Cite
|
Sign up to set email alerts
|

Internet Survey of Japanese Patients With Chronic Constipation: Focus on Correlations Between Sleep Quality, Symptom Severity, and Quality of Life

Abstract: Background/AimsChronic constipation and lifestyle factors can affect sleep quality. We evaluated the relationship between chronic constipation and sleep in the Japanese population. MethodsThis cross-sectional internet-based survey included 3000 subjects with constipation, classified according to sleep status (good/poor). Primary endpoints were Bristol stool form scale (BSFS) score and correlations between sleep disorder criteria of the Pittsburgh Sleep Quality Index (PSQI) and sleep status (good/poor sleep). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
2
7
0
3
Order By: Relevance
“…Although the relationship between SD and DGBI is incompletely understood, latest studies indicated that there were close associations of SD with lower gastrointestinal symptoms. In a cross-sectional internet-based survey for Japanese population, Yamamoto et al (2021) tested the relationship between chronic constipation and sleep and the authors demonstrated that subjects with constipation and poor sleep experienced severe symptoms and had poor quality of life, which is consistent with our findings. Jiang et al (2017) investigated 126 patients with chronic constipation and reported that patients with sleep disorders had worse constipation symptoms evaluated by the constipation scoring system (CSS) scale, compared to those without sleep disorders ( P = 0.031).…”
Section: Discussionsupporting
confidence: 87%
“…Although the relationship between SD and DGBI is incompletely understood, latest studies indicated that there were close associations of SD with lower gastrointestinal symptoms. In a cross-sectional internet-based survey for Japanese population, Yamamoto et al (2021) tested the relationship between chronic constipation and sleep and the authors demonstrated that subjects with constipation and poor sleep experienced severe symptoms and had poor quality of life, which is consistent with our findings. Jiang et al (2017) investigated 126 patients with chronic constipation and reported that patients with sleep disorders had worse constipation symptoms evaluated by the constipation scoring system (CSS) scale, compared to those without sleep disorders ( P = 0.031).…”
Section: Discussionsupporting
confidence: 87%
“…In 350 BC, Astoria elaborated in his book Sleep and Insomnia that sleep is caused by hot steam produced by the stomach during digestion [ 44 ]. Some studies have shown a two-way link between chronic constipation and sleep quality, i.e., sleep disturbances may affect bowel function and increase the risk of gastrointestinal disorders, and constipation may also affect sleep quality [ 45 , 46 ]. In our study, the same results were found in university students, i.e., there was an association between FC and sleep status in university students, with those suffering from FC experiencing poor sleep status.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that poor sleep quality is a risk factor for constipation and other GI symptoms. 57,58 Sleep quality is closely related to anorectal sensitivity, autonomic nervous function, and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, inactivity may aggravate the occurrence and development of constipation and its overlapping symptoms. Studies have also shown that poor sleep quality is a risk factor for constipation and other GI symptoms 57,58 . Sleep quality is closely related to anorectal sensitivity, autonomic nervous function, and mental health.…”
Section: Discussionmentioning
confidence: 99%